BREAKING DOWN THE GENDER CONSTRUCTION: FEMINIST CRITICISM IN SINAR MATA IBU BY HARRIS EFFENDI THAHAR - Tesaannisa Tesaannisa (KOLONI, 2023)
The division of roles and distinctions between the traits of men and women are products of the construction of gender in a deeply ingrained society. Because each sex can exhibit masculine or feminine traits depending on the circumstance and condition, these roles and characteristics cannot be used as a binary opposition in practice. The short story "Sinar Mata Ibu" features gender roles that are prevalent in our culture. The text of this short story, however, contains resistance that subverts gender construction when viewed from a feminist perspective. This narrative text makes the claim that both women and men can exhibit both feminine and masculine traits. Keywords: gender construction, feminism, short stories, narrative texts